A reconfiguring and self-healing thermoset epoxy/chain-extended bismaleimide resin system with thermally dynamic covalent bonds. (4th July 2018) - Ding, Zhenjie; Yuan, Li; Guan, Qingbao; Gu, Aijuan; Liang, Guozheng
Abstract: Muti-functional shape memory materials based on epoxy resins (EP) with different concentration of chain-extended bismaleimide resins (CBMI) were fabricated. The resulting EP/CBMI polymers have high glass transition temperature (Tg : 93–125 °C), excellent thermal stability and good mechanical property. Unlike traditional shape memory polymers (SMPs), EP/CBMI SMPs are capable of shape reconfiguration and self-healing abilities. EP/CBMI polymers have high cycle-life shape memory property at high temperature, and their original shapes can be quickly recovered within 21 s by thermal activation method. Because of dynamic transesterification, EP/CBMI polymers can exhibit plasticity and reconfigure their shapes when heated to the temperature of dynamic transesterification (200 °C). For the same reason, EP/CBMI polymers also exhibit good healing behavior, and a 77.5–86.5% recovery of fracture toughness can be obtained after the fractured EP/CBMI polymers are healed at 200 °C/2 h. Graphical abstract: Image 1 Highlights: Shape memory thermoset epoxy/chain-extended bismaleimide polymers were fabricated. The resulting polymers contain thermally dynamic covalent bonds. The resulting polymers show high cycle-life shape memory effect at high temperature. The rearrangement of chemical networks leads to shape reconfiguration of polymers. The polymers exhibit good healing ability and mechanical and thermal properties.